Pelaksanaan Rujukan Rawat Jalan Pelayanan Kesehatan Tingkat Pertama Pasien BPJS di UPT Puskesmas Martapura Barat - Nina Rahmadiliyani; Muhammad Khalid Fahrizal Adha (Jurnal Kesehatan Indonesia, 2018)
Health service is implemented gradually since the first level, second level (regional/ city general hospital) which can only be accessed through referral from first level of health service, the third level (provincial/central general hospital) which can only be accessed through referral from first or second level health service, with exception of emergency situation, problem specialty in the regulation of Healthcare Social Security Administrator. This study aims to analyze the implementation of the first-level outpatient health care referral services for BPJS patients at the UPT Puskesmas Martapura Barat. This research uses qualitative research method with case study approach, conducted in the working area of UPT Puskesmas Martapura Barat, using in-depth interviews data collection techniques to two general practitioners, heads of puskesmas, drug managers, nurses, midwives and JKN managers. The results of this study indicate that the reference policy of the UPT Puskesmas Martapura Barat is SK based on the MoU regulated by BPJS, and there is also a diagnosis of BPJS that should be handled by puskesmas, UPT Puskesmas Martapura Barat is still short of doctors, the availability of medicines contained in puskesmas is still a lot of drug shortage, the completeness of health equipment facilities at the puskesmas in general is sufficient, but still needs to be improved, and there are still patients asking for referrals.